2014
DOI: 10.7250/eb.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Well-being in Context of Regional Development

Abstract: -The aim of the paper is to present the methodology and results of some empirical research of the assessment of wellbeing at local level in context of regional development. To achieve the aim, such qualitative and quantitative methods of research as comparing, grouping, graphical analysis and focus group methods were be used. The main result and finding of the paper is the conclusion that in order to promote the regional development of the territory, the assessment of well-being at the level of administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The research showed that well-being is complex concept and different it aspects are crucial for inhabitants. For more analysis of results see Jēkabsone & Sloka (2014) and Jēkansone et al (2013).…”
Section: Figurementioning
confidence: 99%
“…The research showed that well-being is complex concept and different it aspects are crucial for inhabitants. For more analysis of results see Jēkabsone & Sloka (2014) and Jēkansone et al (2013).…”
Section: Figurementioning
confidence: 99%